The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/jvi.76.10.4940-4949.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Echovirus 30: Temporal Circulation and Prevalence of Single Lineages

Abstract: Echovirus 30 (EV30) is one of the most frequently isolated EVs, causing extensive outbreaks of EV30 aseptic meningitis in temperate climates. EV30 is antigenically heterogeneous, and three major antigenic groups have been defined, although the basis for the antigenic differences is unknown. A reverse transcription-nested PCR which amplifies the 3-terminal region of the VP1 gene directly from clinical samples was selected for studying EV30 molecular epidemiology, since the major antigenic sites in this region r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 18 publications
7
74
1
3
Order By: Relevance
“…Comparison of VP1 sequences from previous studies allowed the main clades to be matched to previously assigned genotypes or lineages. The majority (318/325) of variants analyzed in the study fell into previously assigned E30 genotype II cluster of VP1 sequences, with most falling into the H lineage and smaller numbers in the E, F, and G VP1 subgroups designated in previous studies (8,42). These correspond to VP1 lineages classified as C0 to C4 (32) or 3a to 3d (49 VP1 sequences from the main E30 group in the sequenced region of VP1 showed approximately 9% nucleotide sequence divergence (mean pairwise P distance), with variability almost entirely restricted to synonymous sites (nonsynonymous to synonymous substitution [dN/dS] ratio based on uncorrected synonymous and nonsynonymous distances of 0.04).…”
Section: Sequence Diversity Of E30mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of VP1 sequences from previous studies allowed the main clades to be matched to previously assigned genotypes or lineages. The majority (318/325) of variants analyzed in the study fell into previously assigned E30 genotype II cluster of VP1 sequences, with most falling into the H lineage and smaller numbers in the E, F, and G VP1 subgroups designated in previous studies (8,42). These correspond to VP1 lineages classified as C0 to C4 (32) or 3a to 3d (49 VP1 sequences from the main E30 group in the sequenced region of VP1 showed approximately 9% nucleotide sequence divergence (mean pairwise P distance), with variability almost entirely restricted to synonymous sites (nonsynonymous to synonymous substitution [dN/dS] ratio based on uncorrected synonymous and nonsynonymous distances of 0.04).…”
Section: Sequence Diversity Of E30mentioning
confidence: 99%
“…Further from Europe, in Southeast Asia, E30 variants in Malaysia (this study), Taiwan (11), and China (60) Because of the number of sequences (Ͼ300), only those showing greater than 1.0% or 1.5% divergence, respectively, from each other are shown. Dot colors indicate the 3Dpol clade of the displayed sequences (see text), not the H, E, F, and G VP1 subgroups assigned in previous analyses (8,42). 3Dpol region sequences of study subjects were interspersed with sequences from other species B serotypes and have been included in panel B, labeled with the following abbreviations: E, echoviruses; CVA, coxsackie virus type A; CVB, coxsackie virus type B; EV, new enteroviruses.…”
Section: ϫ3]mentioning
confidence: 99%
“…Since its characterization in 1958, E30 has been increasingly associated with meningitis outbreaks worldwide [88]. Several studies have shown different clustering of E30 variants based on VP1 and/or 5' UTR sequences [18, [89][90][91].…”
Section: Molecular Epidemiology Of Non-polio Enterovirusesmentioning
confidence: 99%
“…Following principles previously applied in Echovirus 30 analysis (Palacios et al, 2002), EV-C105 strains were divided into lineages based on pairwise distances: (1) lineage A consisting of Pavia/8376, Pavia/9095 and ROM31 strains and (2) lineage B including BU77 and BU5 strains. The distribution of pairwise distances along the entire genome was similar for the three European EV-C105 strains (group A), while the degree of nucleotide identity between the African strains (group B) and the reference strain (34S) for the P2 and P3 regions (81.8-83.2 %) was lower than that for the P1 region (83.9-84.0 %).…”
mentioning
confidence: 99%